Protective Effect of Lithium Chloride on EndotheliaL Cells in Septic Shock - O. A. Grebenchikov; V. T. Dolgikh; M. D. Prokofiev; I. S. Kasatkina; A. V. Ershov (Общая реаниматология)
The aim is to study the effectiveness of lithium chloride for preventing damage to the monolayer of endothelial cells in vitro exposed to serum of patients with septic shock.Material and methods. Serum samples prepared from blood of 5 septic shock patients selected according to «Sepsis-3» criteria and 5 healthy volunteers (control serum) were used in the study. Blood for experiments was withdrawn within 2 hours after the diagnosis of septic shock. The Ea.hy926 endothelial cells were incubated with the serum of a patient with septic shock (toxic serum) or control serum for 3 hours at 37°C without or with lithium chloride at final concentrations of 0.01 mmol/l, 0.1 mmol/l, 1 mmol/l, 10 mmol/l. Lithium chloride was added 1 hour before the serum change. After incubation, the expressions of actin, VE-cadherin and claudin were assessed by immunofluorescent microscopy; the level and degree of phosphorylation of glycogen synthase kinase 3/1 (GSK-3/3) were determined using western blotting.Results. Toxic serum significantly inhibited GSK-3/3 phosphorylation, induced cleavage of VE-cadherin and reduced the claudin inendothelial cells. Toxic serum also altered the shape of endothelial cells: they lost their native polygonal shape and became elongated with gaps between them. Incubation of endothelial cells monolayer with lithium chloride at concentrations equal or higher 1.0 mmol/l almost completely prevented cleavage of claudin, actin and VE-cadherin. When studying the in vitro protection of endothelial cells from effects of toxic serum with lithium chloride, pre-incubation with the drug at a concentration of 1 mmol/l for 1 hour prevented inactivation (dephosphorylation) of GSK-3/3 and even to stimulate its phosphorylation in 1-4 hours after exposure to the serum.Conclusion. The study clearly showed the protective effect of lithium chloride on endothelial cell monolayer by activating phosphorylation of GSK-3/3 (enzyme conversion into inactive form). Moreover, the effect of lithium chloride exhibited a distinct dose-dependent character starting with a concentration of 0.01 mmol/l.